Levothyroxine Tablet Malabsorption Associated with Gastroparesis Corrected with Gelatin Capsule Formulation - Reardon, David P. (Case Rep Endocrinol, 2016)
Treatment of hypothyroidism with levothyroxine sodium often requires multiple dose adjustments and can be complicated by patients with gastric and intestinal dysfunction that limits absorption. In these cases, doses are often titrated higher than commonly used in clinical practice. Multiple formulations of levothyroxine are currently available and some may be preferred in cases of malabsorption. We report a case of a 42-year-old female who presented with a living unrelated kidney transplant evaluation with myxedema while being treated with levothyroxine sodium tablets. She was noted to have gastroparesis secondary to Type I diabetes mellitus which may have contributed to levothyroxine malabsorption. Changing to a gelatin capsule formulation quickly corrected her thyroid function assays. This case suggests that gastroparesis may affect absorption of levothyroxine tablets and the gelatin capsules may be an effective alternative therapy.